Process in family business internationalisation: The state of the art and ways forward - Metsola J; Leppäaho T; Paavilainen-Mäntymäki E; Plakoyiannaki E (ELSEVIER, 2022)
Although the internationalisation of family businesses (FBs) has received increasing attention in recent years, much remains to be learned about how FB internationalisation unfolds as a process. Our review of 172 empirical studies from the period of 1991-2018 indicates that only 25 studies included both longitudinal data and strong process theorising, even though internationalisation is inherently processual, and FBs are longitudinal in nature. We acknowledge that both variance-and process-based theorising are needed to build an understanding of the FB internationalisation process. We contribute to the field by building an FB internationalisation process model based on a review analysis. Within the model, process-based internationalisation pathways are combined with variance-based capabilities (positive influences) and liabilities (negative influences) that affect internationalisation, with economic and non-economic goals viewed as driving the various internationalisation processes. On the basis of the model, we suggest that future research could adopt more longitudinal and individually focused approaches, as a means to understand the FB internationalisation process in various FBs and contexts, over various time periods, life cycles, and FB generations.